Challenges in Applied Linguistics and Language Teaching in the 21st Century: A Literature Review - Fadilla Rusdi, Hanna (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Due to globalization and technological improvements, applied linguistics and language teaching have seen significant changes in the twenty-first century. A literature review on the challenges in 21st-century applied linguistics and language teaching is given in this paper. It discusses some issues such how technology is integrated into language classes, how globalization affects language instruction, and how the requirements of multicultural and multilingual students are changing. This paper also discusses pedagogical issues, such as how to modify instruction to suit different learning styles, how to effectively educate teachers, and how to create evaluation plans that complement communicative skills. Furthermore, it also examines how research influences language teaching methods and talks about potential solutions to these problems in the future. Thus, the results indicate that even though there has been a lot of progress, more work is needed to address the dynamic and complicated character of language education in a world that is changing quickly.